2016
DOI: 10.1371/journal.pone.0165837
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction of Pneumonia in Acute Stroke Patients Using Tongue Pressure Measurements

Abstract: Swallowing dysfunction caused by stroke is a risk factor for aspiration pneumonia. Tongue pressure measurement is a simple and noninvasive method for evaluating swallowing dysfunction. We have hypothesized that low tongue pressure may be able to predict pneumonia occurrence in acute stroke patients. Tongue pressure was measured using balloon-type equipment in 220 acute stroke patients. The modified Mann Assessment of Swallowing Ability (MASA) score was evaluated independently on the same day. Tongue pressure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 24 publications
4
68
1
Order By: Relevance
“…Studies with post-stroke patients (6,18,19) also found that the mean and maximum tongue pressure was significantly lower in the dysphagia group. Thus, the decrease in tongue pressure observed in some cases of stroke was basically associated with the presence of dysphagia.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Studies with post-stroke patients (6,18,19) also found that the mean and maximum tongue pressure was significantly lower in the dysphagia group. Thus, the decrease in tongue pressure observed in some cases of stroke was basically associated with the presence of dysphagia.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, it is a resource that can be used at the bedside and can predict the occurrence of pneumonia if the pressure is below 21.6 kPa (6) . Therefore, the analysis of the pressure of the tongue should be an aspect valuable and approached therapeutically during rehabilitation from dysphagia, in addition to other alterations found.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations